Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.082
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Intention to Use Commercial Bike-sharing Systems: An Integration of TAM and TPB

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 48 publications
(73 reference statements)
4
33
0
Order By: Relevance
“…A research conducted by Muñoz-Leiva et al, [22] found that PEOU has a significant positive relationship with AT towards new mobile banking application system. Research by Yu, Yi, Liu, & Feng, [23] also found that AT toward use of Commercial Bike-sharing Systems was positively affected by PEOU. Additionally, a study by Sarika, Preeti, Shilpy, & Sukanya, [24] found that PEOU of the system has a positive relationship towards AT to shop online.…”
Section: Research Objectivesmentioning
confidence: 92%
“…A research conducted by Muñoz-Leiva et al, [22] found that PEOU has a significant positive relationship with AT towards new mobile banking application system. Research by Yu, Yi, Liu, & Feng, [23] also found that AT toward use of Commercial Bike-sharing Systems was positively affected by PEOU. Additionally, a study by Sarika, Preeti, Shilpy, & Sukanya, [24] found that PEOU of the system has a positive relationship towards AT to shop online.…”
Section: Research Objectivesmentioning
confidence: 92%
“…Various items were examined such as value and residual effects [26], past behavior, personal norm [27], and attractiveness of unsustainable alternatives [28], and technology acceptance model (TAM) with TPB etc. [29] [30]. Moreover, Kaplan et al [11] used TPB in bicycle tourism.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Bicycling is a non-motorized and low-emission transport mode. The wide use of cycling can reduce energy consumption and carbon emissions, thus improving the urban environment [5]. The bicycle-sharing system is revolutionizing urban transportation systems and mobility modes [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results show: (1) overall transit usage continued growing after the shared bicycles market reached a plateau; (2) short public transits within 2 km decreased while transfers within 2 km increased; and (3) the decrease of short transits and increase of transfers within 3 km were spatially highly correlated to the usage of shared bicycles. Hence, the role of bicycle-sharing systems is competitive for existing public transit systems during short trips and cooperative for connecting transits.bicycles for short commutes, tourism, and exercise [5]. In the last few years, millions of shared bicycles purchased by companies have quickly flooded into urban areas; therefore, how and to what extent the shared-bicycle system will influence existing public transit systems has become a concern for researchers [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation